AN ASSESSMENT OF THE CONTRIBUTIONS OF SOKOTO JIHAD LEADERS TO GOOD GOVERNANCE - Faruk Siddik Tilli (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
The research paper an assessment of the contribution of Sokoto Jihad leaders to good governance is aims at reveal the Contributions of the Leaders of Sokoto Jihad to good governance. It studied the literature of activities of the Jihad leaders and their practice of good governance. The Jihad carried out by prominent Muslim Scholars and reformers under the leadership of Shaykh Usmanu Dan Fodiyo was a significant historical event that shaped the political landscape of the region that is now called northern Nigeria in the nineteenth century. The paper also looked at the political situation of Hausaland before the Jihad and how it was administered before the emergence of the Sokoto Caliphate. This study seeks to explore the role played by these Leaders in promoting good governance principles and its impact on the socio-political development of Hausaland. The paper employs a qualitative research methodology, utilizing historical analysis and literature review. Primary and secondary sources such as historical texts, scholarly writings and relevant documents were consulted to gather the required information.